1969
DOI: 10.12669/pjms.322.8978
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Quantitative and Qualitative Detection of BK and JC Virus in Blood and Urine of Renal Transplantation Recipients

Abstract: Objective:To evaluate value of quantitative and qualitative detection of BK virus (BKV) and JC virus (JCV) in timely diagnosing polyomavirus-associated nephropathy (PVAN) occurring inrenal transplantation recipients.Methods:We collected 306 cases of urine specimen and 310 cases of blood specimen from 306 patients who underwent renal transplant. Levels of BKV and JCV in blood and urine were detected using real-time quantitative polymerase chain reaction (PCR).Results:Detection rate of BKV DNA was 33.3% (102/306… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Then PCR amplification was performed on a ABI7500 instrument (ThermoFisher Scientific, Waltham, MA))with a thermocycling profile at 37°C for 2 min,95°C for 3 min followed by 40 cycles at 94°C for 15 sec, and at 60°C for 35 sec. The detection limit was determined at 2000 copies/mL[17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then PCR amplification was performed on a ABI7500 instrument (ThermoFisher Scientific, Waltham, MA))with a thermocycling profile at 37°C for 2 min,95°C for 3 min followed by 40 cycles at 94°C for 15 sec, and at 60°C for 35 sec. The detection limit was determined at 2000 copies/mL[17].…”
Section: Methodsmentioning
confidence: 99%
“…In immunosuppressed individuals,BK virus reactivation may cause kidney (BK-associated nephropathy) or bladder (hemorrhagic cystitis and ureteral stenosis) injury [6].The infection occurs in the following chronological stages-viruria, viremia, and allograft nephropathy [7,8] .Viruria and viremia are detected in approximately 30% and 12% of kidney transplant recipients, respectively [9,10] .Measuring BKV DNA in urine and serum is a useful and noninvasive tool for early detection and monitoring [11]. urine BK viral loads >8 log10 c/mL predict the onset of viremia, while plasma BK viral loads >4 log10 c/mL are associated with higher rates of biopsy-proven BKVAN [12][13][14] .Antiviral immunoregulatory markers like Gamma interferon (IFN-γ) might also affect the polyomavirus BK pathogenesis for its role in antiviral host defense, graft rejection, and regulative of the adaptive immune responses.Recent reports have shown that CD4+T cells likely have a direct role in controlling BKV infection, mediated through the expression of proinflammatory cytokines, including IFN-γ and tumor necrosis factor (TNF), and via the expression of the cytolytic molecule granzyme B [15].Analysis of the results showed that IFN-γ (rs12369470) CC genotype was significantly associated with susceptibility to BKV infection,it means Polymorphisms in the IFN-γ gene may confer certain protection or predisposition for BKV infection [16].Currently, the commonly used detection method includes detection of decoy cells in urine at cytological level, detection of DNA in urine and blood with polymerase chain reaction (PCR) and immunohistochemical examination [17] .Thus we want to find a new way to make an early diagnosis for BKVN with a rapid and effective detection method,as well, this method can intuitively reflect the severity of renal inflammation, highlighting the need for early intervention and therapy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, BKV and JCV can be detected in urine, whole blood, plasma, serum, tissues and rarely in cerebrospinal fluid (CSF) 2 . The diagnostic methods include cytological examination, immunofluorescent staining, enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) 7 - 9 . The latter is the method of choice to detect active BKV replication in urine or blood since anti-BKV antibodies detection is not helpful and viral isolation is time-consuming 6 .…”
mentioning
confidence: 99%